2012
DOI: 10.5194/bg-9-4337-2012
|View full text |Cite
|
Sign up to set email alerts
|

Ozone stress as a driving force of sesquiterpene emissions: a suggested parameterisation

Abstract: Abstract. Sesquiterpenes (C 15 H 24 ) are semi-volatile organic compounds emitted by vegetation and are of interest in atmospheric research because they influence the oxidative capacity of the atmosphere and contribute to the formation of secondary organic aerosols. However, little is known about their emission pattern and no established parameterisation is available for global emission models. The aim of this study is to investigate a Central European spruce forest and its emission response to meteorological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 71 publications
4
82
1
Order By: Relevance
“…It is generally believed that isoprenoids can protect the plant against oxidative stress during photosynthesis (Loreto at al., 2001Vickers et al, 2009;Jardine et al, 2012). Within this context, in previously reported work, Norway spruce has been found to regulate its sesquiterpene emission rates according to ambient ozone concentrations (Bourtsoukidis et al 2012), and Karlsson et al (2006) provided statistical evidence of the negative effect of ozone on the stem diameter of mature trees. There is also some evidence to suggest that ozone causes even more damage to vegetation than drought-induced limitation of photosynthesis (Karnosky et al, 2003;Matyssek et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is generally believed that isoprenoids can protect the plant against oxidative stress during photosynthesis (Loreto at al., 2001Vickers et al, 2009;Jardine et al, 2012). Within this context, in previously reported work, Norway spruce has been found to regulate its sesquiterpene emission rates according to ambient ozone concentrations (Bourtsoukidis et al 2012), and Karlsson et al (2006) provided statistical evidence of the negative effect of ozone on the stem diameter of mature trees. There is also some evidence to suggest that ozone causes even more damage to vegetation than drought-induced limitation of photosynthesis (Karnosky et al, 2003;Matyssek et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…General information about the analytical technique can be found in the literature (Lindinger et al, 1998;Blacke et al, 2009, and references therein), while more specific information about the settings of this study can be found in Bourtsoukidis et al (2012). Briefly, the PTR-MS was operated under standard conditions with a drift tube voltage of 600 V and drift tube pressure of 2.3 mbar.…”
Section: Ptr-ms Measurementsmentioning
confidence: 99%
See 3 more Smart Citations